An analysis of the evolution of crown financial statements in New Zealand : a grounded theory approach : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Accountancy at Massey University - Lye, Joanne Margaret (Massey University, 1996)
In April 1992 the Financial Statements of the Government of New Zealand (also called Crown Financial Statements (CFSs)) were published for the six months ended 31 December 1991. These accrual statements consolidated the activities of Government and were prepared in accordance with generally accepted accounting practice (GAAP). This initiative by a sovereign government is believed to be unprecedented in the world in recent times. The initiative occurred within core public sector management reform undertaken in New Zealand since 1987, a subset of broader economic reform that commenced with the election of the Fourth Labour Government in July, 1984. This study investigates how the process of change led to the evolution of CFSs in New Zealand. Grounded theory, an interpretive research strategy, is applied to discover why this initiative was taken in New Zealand. The primary source of data for this study came from interviews with participants involved with the development of CFSs at various stages (i.e., idea initiation, development, approval, and implementation). Interview data were supplemented by searching archival documents, newspaper cuttings collected since the commencement of the study, and the literature. The study provides a substantive theoretical framework to explain many mutually shaping factors that influenced the phenomenon under investigation. All the conceptual categories (Key People. Axial Principles, Communicating Ideas, Contextual Determinants, Ethos, Knowledge, Process of Change, Synergistic Process of Change, Innovation, Action, Information and Consequences) illustrated in the framework are defined and explained with supporting extracts from interview data. The contribution of this study is twofold. First, it offers a new way of understanding accounting by developing a framework that incorporates many complex and interdependent factors that influenced the publication of CFSs in New Zealand. Second, the study explains the approach taken and how the research evolved during the research process in a manner that would benefit other similar research. Key Words: Crown Financial Statements; Grounded Theory.
Keywords: New Zealand; Finance, Public; Accounting; Grounded theory; Administrative agencies -- Management; Executive departments - Reorganisation